2016
DOI: 10.1242/dev.140681
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptional regulation of intermediate progenitor cell generation during hippocampal development

Abstract: During forebrain development, radial glia generate neurons through the production of intermediate progenitor cells (IPCs). The production of IPCs is a central tenet underlying the generation of the appropriate number of cortical neurons, but the transcriptional logic underpinning this process remains poorly defined. Here, we examined IPC production using mice lacking the transcription factor nuclear factor I/X (Nfix). We show that Nfix deficiency delays IPC production and prolongs the neurogenic window, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 44 publications
3
65
0
Order By: Relevance
“…Although mRNA expression analyses of Nfia and Nfib knockout embryos have revealed several common downstream targets (Barry et al, 2008;Betancourt et al, 2014;Harris et al, 2016;Piper et al, 2009Piper et al, , 2010Piper et al, , 2014, the overlap of these factors in regulating downstream targets and pathways remained unclear. We therefore analysed mRNA-sequencing data from the cerebral cortex of E16 Nfia and Nfib knockout mice and their corresponding wildtype littermates.…”
Section: Nfia and Nfib Share Regulation Of Downstream Target Genes Inmentioning
confidence: 99%
“…Although mRNA expression analyses of Nfia and Nfib knockout embryos have revealed several common downstream targets (Barry et al, 2008;Betancourt et al, 2014;Harris et al, 2016;Piper et al, 2009Piper et al, , 2010Piper et al, , 2014, the overlap of these factors in regulating downstream targets and pathways remained unclear. We therefore analysed mRNA-sequencing data from the cerebral cortex of E16 Nfia and Nfib knockout mice and their corresponding wildtype littermates.…”
Section: Nfia and Nfib Share Regulation Of Downstream Target Genes Inmentioning
confidence: 99%
“…As a result, in Nfix -/-mice, radial glial stem cells undergo more self-expanding divisions, thereby extending the neurogenic period. This results in the production of more neurons and postnatal macrocephaly in this line without any observed negative affects on neuronal survival (Chapter 3) Heng et al, 2014;Harris et al, 2016a). In contrast, in AH-NSCs we found that the deletion of Nfix does not affect the production of IPs ( NFIX has been hypothesised to be a central factor in maintaining AH-NSC quiescence.…”
Section: Discussionmentioning
confidence: 77%
“…Two pivotal differences are the relative stages of neuronal lineage progression controlled by NFIX and the effect that Nfix deletion has on neuronal survival. In the developing dorsal forebrain, NFIX promotes the asymmetric division of radial glial stem cells and the subsequent production of IPs (Harris et al, 2016a), which is the earliest fate choice that occurs during neuronal differentiation. As a result, in Nfix -/-mice, radial glial stem cells undergo more self-expanding divisions, thereby extending the neurogenic period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations